Prevalence and associated factors of intraoperative Nausea and Vomiting of mothers who gave birth with cesarean section under regional anesthesia: a systematic review and meta-analysis; 2023 - Basazinew Chekol Demilew; Negesse Zurbachew; Nega Getachew; Getachew Mekete; Diriba Teshome (BMC Pregnancy and Childbirth)
Abstract Introduction Cesarean section is one of the most common obstetric procedures performed worldwide under spinal anesthesia which is a commonly practiced rapid, simple, and safe method. Vomiting and nausea are frequent side effects of many surgical procedures. However, with cesarean sections performed under regional anesthesia, this issue occurs even more frequently. The existing evidence regarding the prevalence and associated factors of intraoperative nausea and vomiting is inconsistent. Therefore, this systematic review and meta-analysis aimed to determine the pooled prevalence and associated factors of intraoperative nausea and vomiting. Methods This is a systematic review and meta-analysis study that was done based on studies published within the last 10 years on the prevalence and associated factors of intraoperative nausea and vomiting during cesarean section under regional anesthesia. After PubMed, Google Scholar, HINAR, Scopus, Science Direct, and grey literature extensive search for primary studies, their quality was assessed with JBI and modified Newcastle Ottawa appraisal assessment tool and data was extracted. STATAMP version 17.0 was used for all possible analyses of the study. Results Twenty-nine studies were met the inclusion criteria of this systematic review and meta-analysis. However, only 21 studies were included by excluding eight studies due to inappropriate method & outcomes and language other than English. The pooled prevalence of intraoperative nausea and vomiting was 36% (95% CI- 31%, 41%) with heterogeneity (I2-93.1%). Premedicated with metoclopramide, uterus exteriorization, motion sickness, preeclampsia, and intraoperative propofol were associated with the prevalence of intraoperative nausea and vomiting significantly. Conclusion The pooled prevalence of intraoperative nausea and vomiting during cesarean section under regional anesthesia was high (36%) which needs more strategies for prevention.